Copper in the colorectal cancer microenvironment: pioneering a new era of cuproptosis-based therapy - Feng, Qixuan; Sun, Yue; Yang, Zhe; Wang, Zhiyu; Chen, Zhangyi; Liu, Fang; Liu, Lingxiang (Frontiers in Oncology, 2025)
Copper, an essential trace element and biochemical cofactor in humans plays a critical role in maintaining health. Recent studies have identified a significant association between copper levels and the progression and metastasis of cancer. Copper is primarily absorbed in the intestinal tract, often leading to an imbalance of copper ions in the body. Colorectal cancer (CRC), the most common cancer originating in the intestines, thrives in an environment with elevated copper concentrations. Current research is focused on uncovering the relationship between copper and CRC which has introduced new concepts such as cuproplasia and cuproptosis, significantly deepening our understanding of copper’s influence on cell proliferation and death. Cuproplasia is a kind of cell proliferation mediated by the co-regulatory activities of enzymes and non-enzymatic factors, while cuproptosis refers to cell death induced by excessive copper, which results in abnormal oligomerization of lipacylated proteins and the reduction of iron-sulfur cluster proteins. Exploring cuproplasia and cuproptosis opens new avenues for treating CRC. This review aims to summarize the critical role of copper in promoting colorectal cancer, the dual effects of copper in the tumor microenvironment (TME), and strategies for leveraging this unique microenvironment to induce cuproptosis in colorectal cancer. Understanding the relationship between copper and CRC holds promise for establishing a theoretical foundation for innovative therapeutic strategies in CRC.